Thank you for the opportunity to help you with your question!

a + 1 = sqrt(b + 1) so :

(a + 1)² = (sqrt(b + 1))² so :

a² + 2a + 1 = b + 1 so :

b = a² + 2a + 1 - 1 so :

b = a² + 2a = a(a + 1 )

jjust ask if theres something not clear

please invite me each time you have any other homework i will give you the best answer

Good Luckk

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up